Occult Hepatitis B Virus Infection in a Previously Vaccinated Injection Drug User - Powell, Eleanor A. (Hepat Mon, 2016)
INTRODUCTION: Occult hepatitis B virus (HBV) is defined by the presence of HBV DNA in patient sera in the absence of HBsAg. Occult HBV has been associated with hepatocellular carcinoma, reactivation during immune suppression, and transmission to others. While the hepatitis B vaccine is very effective at preventing chronic HBV infection, recent studies indicate it is less effective at preventing occult HBV following infant vaccination. No studies, however, have examined the efficacy of adult HBV vaccination at preventing occult HBV. Here, we present the first report of occult HBV following adult vaccination. CASE PRESENTATION: A 21-year old Caucasian female presented with tricuspid valve endocarditis secondary to methicillin-susceptible Staphylococcus aureus with non-ischemic cardiomyopathy. She reported active use of intravenous drugs. Her liver enzymes were elevated (ALT = 1873 IU/mL; AST = 4518 IU/mL), and she was found to have HCV and occult HBV. HBV viral loads ranged from 4608 - 8364 copies IU/mL during hospitalization. The patient’s HBV was sequenced and found to be genotype D3 without any known diagnostic escape mutations. Immune complexes that may have prevented HBsAg detection were not observed. CONCLUSIONS: HBV vaccination in infancy is effective at preventing chronic HBV infection but is less effective at preventing occult HBV infection. Similar studies examining the efficacy of adult HBV vaccination in preventing occult HBV have not been performed. This case highlights the importance of carefully determining the HBV status of high-risk individuals, as vaccination history and the presence of anti-HBs may not be adequate to rule out HBV infection, even in the absence of HBsAg.